Experimental Study on the Effect of In/Out Radial-Finned Heat Sink with PCM under Constant and Intermittent Power Mode in Power LEDs - Thangamani Ramesh; Ayyappan Susila Praveen; Praveen Bhaskaran Pillai; Sachin Salunkhe; Adham E. Ragab; Hussein M. A. Hussein; Paulo Davim (International Journal of Photoenergy)
The findings of the experimental study into optimizing the heat transfer rate of a PCM-based heat sink for high-power LEDs are presented in this work. The study investigated five heat sink types, with and without PCM. The LED case and junction temperatures, LED module temperatures, heat storage and release rate analyses, analyses of three types of cyclic operation modes, luminous flux, and heat sink thermal resistance were all examined independently. The results indicated that the PCM-based LED heat sink had improved thermal performance. The LED junction temperature of the PCM-equipped E-20 heat sink is nine degrees Celsius lower at 10 W than that of the heat sink without PCM. Furthermore, the E-20 heat sink with PCM extends the LED module’s critical lifespan. As a bonus, the E-20 with PCM had a 38.19 percent lower thermal resistance at 10 W than the E-20 without PCM. According to these results, the heat sink E-20 emits 715 lm at 10 W when operated without a phase-change material (PCM). With the same input power, the luminous flux of an E-20 equipped with a heat sink and a phase-change material (PCM) is 750 lm, a gain of 4.7%. Finally, clearly recommend the heat E-20 sink with PCM suitable for high-power LED thermal management system.